PEMBELARAN DISCOVERY BERBASIS PROYEK UNTUK MENGUKUR LITERASI SAINS SISWA - Purwanti, Linda; Sujana, Atep; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2017)
This research aims to see discovery learning based project to measure literacy science students. The methods used in this research is a method of pre-experimental. With the subjectÂ of research grade V SDN Karapyak 1. The research design used is a draft of one group prates and pascates. The research results showed that: (1) dicovery learning based project can be implemented with very good in grade V SDN Karapyak 1. (2) discovery learning based project can improve science literacy grade V SDN Karapyak 1. (3) discovery learning based project can improve science literacy of the students in groups of high, medium and low. (4) there is a significant difference between the groups of high-medium, and high â€“low. While the increase in the groups medium-low difference is not significant.